Novel Anti-inflammatory Treatments in Cirrhosis. A Literature-Based Study - Kronborg, Thit Mynster; Ytting, Henriette; Hobolth, Lise; Møller, Søren; Kimer, Nina (Frontiers in Medicine, 2021)
Liver cirrhosis is a disease characterised by multiple complications and a poor prognosis. The prevalence is increasing worldwide. Chronic inflammation is ongoing in liver cirrhosis. No cure for the inflammation is available, and the current treatment of liver cirrhosis is only symptomatic. However, several different medical agents have been suggested as potential healing drugs. The majority are tested in rodents, but few human trials are effectuated. This review focuses on medical agents described in the literature with supposed alleviating and curing effects on liver cirrhosis. Twelve anti-inflammatory, five antioxidative, and three drugs with effects on gut microflora and the LPS pathway were found. Two drugs not categorised by the three former categories were found in addition. In total, 42 rodent studies and seven human trials were found. Promising effects of celecoxib, aspirin, curcumin, kahweol, pentoxifylline, diosmin, statins, emricasan, and silymarin were found in cirrhotic rodent models. Few indices of effects of etanercept, glycyrrhizin arginine salt, and mitoquinone were found. Faecal microbiota transplantation is in increasing searchlight with a supposed potential to alleviate cirrhosis. However, human trials are in demand to verify the findings in this review.